PEMBIMBINGAN DAN PENDAMPINGAN PERSIAPAN KSN DAN KOMPETISI BIDANG MATEMATIKA LAINNYA DI MADRASAH ARIFAH: GUIDANCE AND SUPPORT FOR PREPARATION FOR NATIONAL STUDENT COMPETITION (KSN) AND OTHER MATHEMATICS COMPETITIONS AT MADRASAH ARIFAH - Syamsuddin Mas'ud (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service activities carried out at Madrasah Arifah for the MTs level aim to enhance the quality of students in competing in the field of mathematics and improve the skills of mathematics teachers in providing guidance to their students. These activities are considered crucial, given that at the MTs level, there are at least two popular competitions, namely the National Science Competition (KSN) and the Madrasah Science Competition (KSM). To achieve these goals, guidance is provided to students involving their mathematics teachers. When students receive guidance, their mathematics teachers also participate in the same class to listen to the material and observe the guidance process. The involvement of teachers in guiding students is expected to contribute to the additional skills of teachers in guiding students. Students who participate in this mentoring program take part in KSN and KSM, achieving success up to the Provincial level in the KSM selection stage and not progressing to the Provincial level in the KSN.